MERANCANG LEMBAGA PEMASYARAKATAN KEROBOKAN DENPASAR SEBAGAI DAYA TARIK WISATA - Kusumasanjiwani, P.; Mahagangga, I G.A.O.; Pujani, L.P.K.; Anom, I P.; Nugroho, S. (Buletin Udayana Mengabdi, 2017)
To minimize crime action in Bali are proper coaching system correctional target and effective so that the inmates after serving his sentence at the jail as Correctional Institution Class IIa Kerobokan Denpasar, realizing his mistake and not repeat it again with the approach of tourism. This is very important because if left unchecked each year will continue to "born" criminals new modes and variations criminality new one anyway (school of crime). Devotion method used is through dialogue-focused dissemination so that the results of research about Kerobokan Prison before can be known and understood by policy holders and staff in Kerobokan Prison in Denpasar. Results Devotion is the Denpasar Kerobokan Prison began to know the role and relationship guidance to prisoners to tourism in Bali. It's just still felt difficult to realize because of Kerobokan Prison Denpasar part of a large system of the Ministry of Justice and Human Rights Affairs. So that requires legal protection and command center for the implementation of new programs such as the development of Kerobokan Prison as a tourist attraction.